The measurement lens matters: considering the sensitivity of the gang effect to coding across samples - McGloin, Jean Marie (Journal of developmental and life-course criminology, 2023)
It is well established that gang membership is associated with an increase in deviant behavior. This “gang effect” is established with a binary measure of whether an individual is in a gang or not; however, this measurement approach contrasts with a life course view that acknowledges the transitions in and out of gang membership involve changes to many domains of life and may have different relationships with offending outcomes. This study investigates whether there is added value from adopting measures of gang membership stages rather than a traditional binary approach. Using within-individual analyses with panel data from three separate datasets (National Longitudinal Study of Youth, Rochester Youth Development Study and Pathways to Desistance Study), our results suggest that a more nuanced measurement approach including gang membership statuses offers important meaningful insight that would be lost with an aggregate, binary approach. Indeed, relying on a binary measure can lead to overly simplistic inferences regarding the relationship between gang membership and criminal outcomes.